2010
DOI: 10.3155/1047-3289.60.5.574
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method for Estimating Surface Fine Particle Concentrations Using Seasonally Adjusted Satellite Aerosol Optical Depth

Abstract: Using satellite observations of aerosol optical depth (AOD) to estimate surface concentrations of fine particulate matter (PM 2.5 ) is a well-established technique in the air quality community. In this study, the relationships between PM 2.5 concentrations measured at five monitor locations in the Baltimore, MD/Washington, DC region and AOD from Moderate Resolution Imaging Spectroradiometer (MODIS), Multi-Angle Imaging Spectroradiometer (MISR), and Geostationary Operational Environmental Satellite (GOES) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…EngelCox et al, 2004a;Zhang et al, , 2011Hoff and Christopher, 2009;Weber et al, 2010). Studies have shown that the relationship between PM 2.5 and AOD is not always suitable for simple regression models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EngelCox et al, 2004a;Zhang et al, , 2011Hoff and Christopher, 2009;Weber et al, 2010). Studies have shown that the relationship between PM 2.5 and AOD is not always suitable for simple regression models.…”
Section: Introductionmentioning
confidence: 99%
“…They observed the poorest correlation for the southwestern USA, with EPA region number 9 having a correlation coefficient of approximately 0.2. Weber et al (2010) extended the work by In a notable study, van Donkelaar et al (2006) took the alternative approach of using remote sensing and a global transport model to present a global estimate of the long-term average PM 2.5 concentrations between the years 2001 and 2006 using satellite observations of AOD from MODIS to estimate η = PM 2.5 /AOD. The three-dimensional (3D) chemical transport model used was GEOS-Chem (http://acmg.seas.harvard.edu/geos/), and the authors found a significant spatial agreement with their estimates; the correlation coefficient for North American PM 2.5 measurements was 0.77 and elsewhere 0.83.…”
Section: Introductionmentioning
confidence: 99%
“…AOD-PM 2.5 regression as was pointed by past studies 8,12 and highlights problems in determining a single regression line for accurately computing PM 2.5 from AOD data. To avoid problems with the AOD-PM 2.5 regression, another approach is proposed for utilizing the multiyear AOD data in air quality applications.…”
Section: Pm 25 and Aod Analysismentioning
confidence: 80%
“…The reported correlations showed a high degree of agreement, yet there was still interstate and intrastate variation. Research from Weber et al 12 recommends that seasonality and different platforms should be included in analysis of the PM 2.5 -AOD relationship.…”
Section: Technical Papermentioning
confidence: 99%
“…Satellite observations of AOD to estimate PM exposures provide more complete spatial and temporal coverage than fixed monitoring sites [20][21][22][23][24][25], but the existing methods using AOD are still limited to the resolution of the instrument's aerosol product retrieval algorithm. Fortunately, the spatial resolutions of satellite aerosol products have improved dramatically since their inception.…”
Section: Introductionmentioning
confidence: 99%